The application of the biological treatment in atopic dermatitis: focus on dupilumab - Yu. S. Smolkin; S. S. Masalskiy; O. Y. Smolkina (Аллергология и Иммунология в Педиатрии)
Atopic  dermatitis (AD) significantly reduces the quality of life of patients. Skin lesions, itching, and sleep dysfunction lead to impaired social adaptation and work performance.Systemic immunosuppressants are used for  the treatment of  severe AD.  The use of  antihistamines and  antileukotrienes in the  monotherapy or the  combination with  topical  steroids  is not  recommended and  not  effective for  treatment AD.  This group of medicine drugs applied  in the cases of the сo-morbidity with allergic rhinitis, food  allergy and asthma.If it is necessary to use systemic drugs for the treatment of severe dermatitis, the appointment of biological therapy (anti-IL4Rα) is recommended from  the  12  years.  Dupilumab has  a high-efficiency profile  (LIBERTY and  ADOL study): by 12–16 weeks  in children,  about  80%  of  patients have  an EASI  index  halved,  about  half  of  patients report  a decrease  in EASI<75% of the initial values. Dupilumab in recommended doses-200 mg (≤60 kg; ≤18 years) or 300 mg 2 times a month relieves skin lesions, itching and significantly improves  the quality of life of patients. Serological markers of allergic inflammation (IgE, periostin,  chemokine CCL17) are reduced  during  treatment.Clinical studies  (CHRONOS) showed no serious side effects and a decrease in the frequency of skin infections and herpetic eczema  when using dupilumab, but a slight increase  in the frequency of non-severe respiratory diseases  and conjunctivitis. Conjunctivitis was not the cause of drug withdrawal according  to research data.  When  co-morbidity dermatitis and asthma, dupilumab reduces the number  of exacerbations of both diseases.Other  monoclonal antibodies (omalizumab, reslizumab, mepolizumab, benralizumab) are not effective for therapy allergic eczema.Cyclosporin at a dose of 2.5–5 mg/kg/day has comparable effectiveness with dupilumab in the 2 weeks of administration. Then cyclosporin's results get worse. Systemic side effects limit the use of cyclosporine for more than  8 weeks. Oral steroids can be prescribed  in a short course for severe exacerbations (0.5–1 mg/kg/day, ≈ 1 week). Dupilumab is the drug of choice for systemic treatment of dermatitis in patients ≥12 years. The long-term safety-effectiveness profile  of dupilumab is better than  any  other systemic treatment. The drug is used for any  phenotype of dermatitis, independently of the increase  in serum IgE.